1986
DOI: 10.1901/jeab.1986.45-297
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Definition in Conditional Discriminations

Abstract: With a customary arrangement of three horizontally aligned stimulus/response keys, two rhesus monkeys learned conditional hue and line discriminations--an "identity-matching" procedure. First, sample stimuli were presented on the center key, and comparison stimuli were presented on the two side keys. Next, the sample was allowed to appear on any one of the three keys, with the comparisons on the remaining two. The change from fixed to variable sample and comparison locations caused the horizontal and vertical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
85
2
26

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 2 publications
12
85
2
26
Order By: Relevance
“…Iversen, 1997;Iversen, Sidman, & Carrigan, 1986;Lionello & Urcuioli, 1998;Lionello-DeNolf & Urcuioli, 2000Sidman, 1992). To illustrate, when subjects are trained using fixed positions (e.g., samples on the center key and comparisons on the two side keys) and then tested using variable positions (e.g., samples presented on one of the side keys and the comparisons presented on the remaining two keys), accuracy is significantly lower than when samples and comparisons maintain fixed positions (e.g., Iversen, 1997;Iversen et al, 1986;Lionello & Urcuioli, 1998). According to Lionello and Urcuioli, control by stimulus location may explain the negative results obtained in tests for emergent relations with the three-key paradigm because, in some cases at least, the locations of samples and comparisons changed during the tests.…”
Section: Discussionmentioning
confidence: 99%
“…Iversen, 1997;Iversen, Sidman, & Carrigan, 1986;Lionello & Urcuioli, 1998;Lionello-DeNolf & Urcuioli, 2000Sidman, 1992). To illustrate, when subjects are trained using fixed positions (e.g., samples on the center key and comparisons on the two side keys) and then tested using variable positions (e.g., samples presented on one of the side keys and the comparisons presented on the remaining two keys), accuracy is significantly lower than when samples and comparisons maintain fixed positions (e.g., Iversen, 1997;Iversen et al, 1986;Lionello & Urcuioli, 1998). According to Lionello and Urcuioli, control by stimulus location may explain the negative results obtained in tests for emergent relations with the three-key paradigm because, in some cases at least, the locations of samples and comparisons changed during the tests.…”
Section: Discussionmentioning
confidence: 99%
“…Although the advantages brought by the specific changes selected in our procedures (i.e., the changes mentioned in the Introduction) remain to be analyzed, some evaluation of possible advantages may be offered. Iversen, Sidman, and Carrigan (1986) carried out an experiment in which the sample was first presented only on the center key, and was then allowed to appear on any one of the three keys, with the comparisons on the remaining two. The change from a fixed to a variable sample and comparison locations caused the line orientations (horizontal and vertical lines) used as controlling stimuli to lose control over the animals' responses.…”
Section: Trainingmentioning
confidence: 99%
“…Previous research has shown that location is a controlling feature of the nominal conditional and discriminative stimuli in tasks such as matching-to-sample (Iversen, 1997;Iversen, Sidman, & Carrigan, 1986;Lionello & Urcuioli, 1998). For instance, Lionello and Urcuioli (1998) trained pigeons to high levels of accuracy on twosample, two-comparison matching tasks with a typical configuration of stimuli: samples on the center key and comparison stimuli on the adjacent (left and right) side keys.…”
mentioning
confidence: 99%